Dampak Trasfer: Teknologi, Manajemen Dan Pemasaran Terhadap Produktivitas dan Biaya Produksi Produj Palm Sugar ( Studi Kasus Koperasi Ar-Ridho Nagari Simpang Tonang Kecamatan Duo Koto, Kabupaten Pasaman, Provinsi Sumatera Barat) - ., Yanuar (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2014)
Limited funds, education and skill levels to make the productivit and quality of SME products in general difficult to complate in the free market. Help management, production technology, and marketing from University can improve the quality, productivity, and product marketing SMEs(coorperative). This sutdy compared the productivity and efficiency of palm sugar products Cooperative Ar-Ridho before after management assitance, technology, production and marketing by Tarumanagara University of Jakarta. The empirical findings of this study are increased productivity and improved efficiency of palm sugar products after the transfer technologycally,management,and marketing